Frank Stinchfield Award: Identification of the At-risk Genotype for Development of Pseudotumors Around Metal-on-metal THAs. Issue 2 (February 2018) - Kilb, Brett K. J.; Kurmis, Andrew P.; Parry, Michael; Sherwood, Karen; Keown, Paul; Masri, Bassam A.; Duncan, Clive P.; Garbuz, Donald S.
Abstract: Background: Once touted as the future of hip arthroplasty, metal-on-metal (MoM) bearing surfaces have fallen sharply from favor with the emergence of a strong body of evidence demonstrating unacceptably high premature implant failure rates. The previously unpredictable development of adverse local tissue reactions (ALTRs) has been a substantive contributor to this. Although the underlying pathophysiology of these so-called "pseudotumors" is now well understood, the fundamental predisposing patient risk factors have remained elusive. Questions/purposes: The aim of this research, as a clinical-genotype correlation analysis, was to identify specific alleles (genes) associated with the development of ALTRs in patients with in situ MoM THAs. Methods: A case-control study of patients who received a large-head, primary MoM THA between 2005 and 2008 was performed with a minimum followup of 5 years. Twenty-six patients who had undergone revision of a primary MoM THA secondary to symptomatic ALTRs were recruited. The mean timeframe from primary MoM THA to symptomatic revision was 5.5 years (range, 1-10 years). Twenty-eight control subjects were randomly selected asymptomatic patients with no evidence of ALTRs on protocol-specific screening. Baseline demographics and high-resolution genotype (human leukocyte antigen [HLA] Class II) were collected for all patients. Cohorts were similar with respect to age at the time of primary MoM THA (mean, 54.8 versus 54.9 years, p = 0.95) and serum cobalt (mean, 5.5 versus 8.5 μg/L, p = 0.09) and chromium concentrations (mean, 2.9 versus 4.2 μg/L, p = 0.27). The association between genotype and revision surgery secondary to ALTRs was determined with gender as a covariate. Results: The prevalence of the risk genotype was 30% (16 of 54) among the entire cohort. Adjusting for sex, the odds of revision were 6.1 times greater among patients with the risk genotype present than among patients without (95% confidence interval [CI], 1.5-25.4; p = 0.01). Among females, the specificity of the risk genotype was 1.0 (95% CIexact, 0.5-1.0; pexact = 0.03), and for males, it was 0.8 (95% CIexact, 0.6-0.9; pexact < 0.01). Conclusions: The findings of this study suggest that, among patients with a primary MoM THA, allelic variation within the HLA Class II loci may be a strong, independent risk factor associated with the need for subsequent revision surgery secondary to pseudotumor formation. Clinical Relevance: Given the hypothesis-generating nature of this novel undertaking, confirmatory prospective clinical studies are required to further elucidate this correlation and to explore the clinical utility of targeted genetic screening in this specific population. This research may, however, represent a key missing piece in the puzzle that is metal ion-induced pseudotumor formation.